Deteksi Dini Faktor Resiko Kehamilan dan Peningkatan Pengetahuan Kader Tentang Screening Serta Pemeriksaan Kesehatan pada Ibu Hamil di Desa Mosso - Nur Anita; Diana, Sitti Aras (Yayasan Inspirasi El Burhani, 2025)
Introduction: Pregnancy risk has a dynamic nature, because suddenly pregnant women who are initially normal can become high risk. Meanwhile, high risk pregnancy is a pregnancy with a greater risk than usual and can cause illness or death before or after childbirth, both for the mother or baby. Objective: Increase public knowledge, especially pregnant women, about risk factors that can affect pregnancy. Method: This community service activity was carried out on Wednesday-Thursday, December 18-19, 2024 starting at 09.00 WITA. Community service activities have been carried out at the Mosso village office hall. As the implementing staff are 4 people consisting of 2 midwifery lecturers and 2 students. The number of pregnant women who attended was 22 people, the number of cadres was 10 people. Result: The results of the Pregnancy Risk Level Examination conducted on 22 pregnant women were 5 (23%) pregnant women who were in the Low Risk Pregnancy category, 11 (59%) pregnant women in the High Risk category, 6 (27%) pregnant women in the Very High category. the results of measuring knowledge about Poedji Rochjati screening, namely Pre-post results show that 100% of cadre mothers do not know about Poedji Rochjati screening and after counseling or socialization obtained Post test results 80% of cadre mothers know about Poedji Rochjati screening and apply it. Conclusion: Useful in increasing the knowledge and ability of cadres in screening risk factors for pregnant women and increasing public knowledge about the importance of early detection of pregnancy risk factors and routine health checks.